Non-enzymatic and enzymatic hydrolysis of alkyl halides: A haloalkane dehalogenation enzyme evolved to stabilize the gas-phase transition state of an S(N)2 displacement reaction - Lightstone, Felice C. (The National Academy of Sciences of the USA, 1997)
The semiempirical PM3 method, calibrated against ab initio HF/6–31+G(d) theory, has been used to elucidate the reaction of 1,2-dichloroethane (DCE) with the carboxylate of Asp-124 at the active site of haloalkane dehalogenase of Xanthobacter autothropicus. Asp-124 and 13 other amino acid side chains that make up the active site cavity (Glu-56, Trp-125, Phe-128, Phe-172, Trp-175, Leu-179, Val-219, Phe-222, Pro-223, Val-226, Leu-262, Leu-263, and His-289) were included in the calculations. The three most significant observations of the present study are that: (i) the DCE substrate and Asp-124 carboxylate, in the reactive ES complex, are present as an ion-molecule complex with a structure similar to that seen in the gas-phase reaction of AcO(−) with DCE; (ii) the structures of the transition states in the gas-phase and enzymatic reaction are much the same where the structure formed at the active site is somewhat exploded; and (iii) the enthalpies in going from ground states to transition states in the enzymatic and gas-phase reactions differ by only a couple kcal/mol. The dehalogenase derives its catalytic power from: (i) bringing the electrophile and nucleophile together in a low-dielectric environment in an orientation that allows the reaction to occur without much structural reorganization; (ii) desolvation; and (iii) stabilizing the leaving chloride anion by Trp-125 and Trp-175 through hydrogen bonding.